Beyond Aesthetic Communication Strategies in Improving the Company's Image Through Social Media - Naori, Erin Arita; Muharman, Deddy (Ilomata International Journal of Management, 2024)
This study aims to analyze the role of social media in Beyond Aesthetics' communication strategy on improving their company image in the competitive world of beauty industry as a medical aesthetic specialist in Indonesia. This study uses qualitative research method, case study methodology and using strategic planning for Public Relations which analyze the situation, strategy, tactics, and evaluative research. To achieve the required information, the company's social media was analyzed and The Director of Sales and Operations and related staff was interviewed to give their in-depth knowledge about the company's communication strategy which resulted in using integrated and proactive communication strategy using educational approach while having a strong understanding of consumer needs and the market's dynamics and quickly adapting with the rapid changes in the industry are the Beyond Aesthetics' social Media Communication Strategy. In conclusion, based on this study, the right media, creating interesting content, and implementing the appropriate communication strategies plays a big role in building a positive company image in the eyes of the stakeholders and ensuring their loyalty for Beyond Aesthetic to reach their success.